1937
DOI: 10.6028/jres.018.013
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative study of methods for the determination of oxygen in steel

Abstract: The data from reports of 35 laboratories, comprising more than 2,000 analytical determinations, indicate that the vacuum-fusion method yields accurate r esults for the oxygen contents of plain-carbon steels either aluminum-killed, siliconkilled, or of the rimming type; the aqueous-iodine method yields accurate results for some types of killed steels and low results for other steels; more data, and particularly more concordant data, are necessary to define the accuracy of the other methods employed in this coop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1941
1941
1968
1968

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Our results agreed with these values, within experimental error, except for the 1040 series of standards. Serious heterogeneity in the oxygen content of these specimens has already been reported and our measurements have confirmed these findings (11, 18). The concentration values listed in Table III for these standards were obtained on the rod sections employed for calibration purposes.…”
Section: Determinationssupporting
confidence: 88%
“…Our results agreed with these values, within experimental error, except for the 1040 series of standards. Serious heterogeneity in the oxygen content of these specimens has already been reported and our measurements have confirmed these findings (11, 18). The concentration values listed in Table III for these standards were obtained on the rod sections employed for calibration purposes.…”
Section: Determinationssupporting
confidence: 88%
“…If the sample is drilled under oil, and the drillings are w'ashed with benzene and stored in a desiccator, the oxygen content of the oxide coating w'ill give an increase of 0.003 to 0.005% in oxygen content of the sample (6, 21). If solid polished pieces are used, the oxide coating is insignificant (1, 38).…”
Section: Mercurymentioning
confidence: 99%
“…Steel 15, without any thermal treatment except that incidental to the hot rolling, contained 0.00010 percent of hydrogen. This value resembles the hydrogen contents of the hot-rolled rods of simple steels rather than that of steel 13. Sample 14, which had been annealed for 8 hours at 735° C, subsequent to hot working, contained 0.00001 percent of hydrogen.…”
Section: Hydrogen Contents Of Miscellaneous Ferrous Materialsmentioning
confidence: 99%
“…Chipman and Fontana [10] in 1935 reported that duplicate determinations of hydrogen might differ by as much as 0.0005 percent. In the cooperative study of methods for the determination of oxygen in steel [13] in 1937, four of the cooperators reported results for hydrogen by vacuum fusion. These results indicated that the hydrogen content of each of the eight selected steels was less than 0.001 percent, but a more accurate value could nOb be indicated.…”
mentioning
confidence: 99%